A STUDY OF USER’S BEHAVIOUR AND ADOPTION WITH REGARD TO TELEGRAM - Amrita Pradhan, Dr. Jesus Milton Rousseau S (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
The research began by exploring user perceptions and behaviours regarding the messaging app Telegram, delving into awareness, usage patterns, preferences, and improvement suggestions. Users were surveyed on their familiarity with Telegram, their usage frequency, awareness of its features, and opinions on the factors influencing their adoption of the platform. Key insights emerged from the conversation, indicating that while a majority of respondents were aware of Telegram, usage frequency varied significantly, with a notable proportion using it rarely or never. Users highlighted various features they appreciated in Telegram, including its large file-sharing capabilities, security measures such as end-to-end encryption and secret chats, and the platform's user-friendly interface. However, opinions on its influence on adoption and preference varied, with some users believing specific features influenced adoption, while others expressed uncertainty or lack of experience. Moreover, users provided a range of suggestions to enhance Telegram's adoption and user experience. These suggestions encompassed improving the user interface, enhancing security measures, offering more customization options, incorporating accessibility features, ensuring cross-platform compatibility, and advocating for educational marketing efforts to promote the app's features. Overall, the research’s insights suggest that while Telegram possesses unique strengths appreciated by users, there is room for improvement in various aspects to attract a broader user base and provide an enhanced user experience. Addressing these suggestions, coupled with effective marketing strategies, could potentially contribute to Telegram's growth and increased adoption among users.